2022
DOI: 10.1007/s10620-022-07401-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Irritable Bowel Syndrome in Medical Staff: A Meta-Analysis

Abstract: Background Irritable bowel syndrome (IBS) is a common functional digestive tract disease worldwide, with a high prevalence among medical staff. The purpose of this study is to systematically evaluate the prevalence and influencing factors of IBS in medical staff. Methods We searched English online databases, including PubMed, The Cochrane Library, Web of Science, Embase, and EBSCOhost. The retrieval time was from database establishment to May of 2021. We screened the literature according to inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Physicians had a high risk of infectious and parasitic diseases or digestive diseases, with ORs of 1.376 and 1.402, respectively. This indicated that physicians were susceptible to digestive diseases, which supports the results of past studies [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Physicians had a high risk of infectious and parasitic diseases or digestive diseases, with ORs of 1.376 and 1.402, respectively. This indicated that physicians were susceptible to digestive diseases, which supports the results of past studies [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Medical professionals' and students' lifestyle is a stressful domain. An MA based on data from seven countries reported a 16% prevalence of IBS among medical staff, which is also comparable to our findings [ 58 ]. We did not find significant differences in IBS prevalence among our study's different groups.…”
Section: Reviewsupporting
confidence: 91%
“…IBS affects the physical and mental health of workers and is associated with work-related issues. Similar to findings in the general population, workers with IBS have reported a lower quality of life, 6–9 a higher prevalence of psychiatric disorders, 10 increased burnout, 11 and significant sleep-related problems, 12 all of which affect their work. 13 , 14 Several studies have highlighted labor productivity issues in workers with IBS, including presenteeism and absenteeism.…”
Section: Introductionsupporting
confidence: 65%
“… 6 , 7 , 13 , 14 The association between IBS and shift work has been previously reported, and some meta-analyses indicate a higher prevalence of IBS among shift workers. 12 , 15 Various treatments for IBS, such as medication 16 and self-management programs, including CBT, 17 can improve the work productivity of individuals with IBS.…”
Section: Introductionmentioning
confidence: 99%